Pulmonary Recruitment Maneuver for Reducing Shoulder Pain after Laparoscopic Gynecologic Surgery: A Network Meta-Analysis of Randomized Controlled Trials - Chumnan Kietpeerakool (2020)
© 2020 Chumnan Kietpeerakool et al. Background. Shoulder pain is a common symptom following laparoscopic surgery. This systematic review was undertaken to assess updated evidence regarding the effectiveness and complications of the pulmonary recruitment maneuver (PRM) for reducing shoulder pain after laparoscopic gynecologic surgery. Methods. A number of databases for randomized controlled trials (RCTs) investigating PRM for reducing shoulder pain were searched up to June 2019. Two authors independently selected potentially relevant RCTs, extracted data, assessed risk of bias, and compared results. Network meta-analyses were employed to simultaneously compare multiple interventions. Effect measures were presented as pooled mean difference (MD) or risk ratio (RR) with corresponding 95% confidence intervals (CI). Results. Of the 44 records that we identified as a result of the search (excluding duplicates), eleven RCTs involving 1111 participants were included. Three studies had an unclear risk of selection bias. PRM with a maximum pressure of 40 cm H2O was most likely to result in the lowest shoulder pain intensity at 24 hours (MD -1.91; 95% CI -2.06 to -1.76) while PRM with a maximum pressure of 40 cm H2O plus intraperitoneal saline (IPS) appeared to be the most efficient at 48 hours (MD -2.09; 95% CI -2.97 to -1.21). The estimated RRs for analgesia requirement, nausea/vomiting, and cardiopulmonary events were similar across the competing interventions. Conclusion. PRM with 40 cm H2O performed either alone or accompanied by IPS is a promising intervention for alleviating shoulder pain within 48 hours following gynecologic laparoscopy.